(untitled) (Research, Society and Development, 2020)
Objective: to review and socialize Standard Operating Procedure (SOP) on the process of disinfecting health products (PPS). Method: An experience report study of an intervention performed in a hospital in the Northwest region of the State of Rio Grande do Sul, in the second semester of 2018, with the participation of the nursing team of the Material and Sterilization Center (CME) and the nurse responsible for the Hospital Infection Control Service (SCIH). The activities took place after contact with the nurse responsible for the unit, who passed on the SOP to be reviewed, there was also the elaboration of a mural on high-level disinfection. Results: five nursing professionals and five academic students who interned at the location participated in the action. It was noticed that two important actions of the PPS disinfection process were not described in the CME POPs, which are: hand hygiene and the use of personal protective equipment (PPE). The team interacted through the exchange of ideas, a principle of permanent health education. Final considerations: The nurse must act as an educator seeking constant updating of his team and solutions for his practice. Finally, the execution of the project made it possible to review the SOPs and discuss with the unit’s team and, in addition, it also showed the need for further studies in this area.